2013
DOI: 10.1080/00223891.2013.825625
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Personality Psychopathology Five Domains OntoDSM–IVPersonality Disorders in Dutch Clinical and Forensic Samples: Implications forDSM–5

Abstract: The Personality Psychopathology Five (PSY-5) model represents 5 broadband dimensional personality domains that align with the originally proposed DSM-5 personality trait system, which was eventually placed in Section III for further study. The main objective of this study was to examine the associations between the PSY-5 model and personality disorder criteria. More specifically, we aimed to determine if the PSY-5 domain scales converged with the alternative DSM-5 Section III model for personality disorders, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
55
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 40 publications
(63 citation statements)
references
References 32 publications
7
55
1
Order By: Relevance
“…This finding indicates that this trait is possibly more peripheral to the AvPD construct and could perhaps explain the co‐morbidity with dependent PD. This finding is also consistent with prior research that has used alternative personality measures, such as the Personality Psychopathology Five, as AvPD was found to be negatively associated with aggressiveness—a construct that in part reflects interpersonal dominance/assertiveness . Aggressiveness was also associated with a lower effect size estimate relative to negative emotionality and introversion/low positive emotionality domains, which represent the core of the disorder …”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This finding indicates that this trait is possibly more peripheral to the AvPD construct and could perhaps explain the co‐morbidity with dependent PD. This finding is also consistent with prior research that has used alternative personality measures, such as the Personality Psychopathology Five, as AvPD was found to be negatively associated with aggressiveness—a construct that in part reflects interpersonal dominance/assertiveness . Aggressiveness was also associated with a lower effect size estimate relative to negative emotionality and introversion/low positive emotionality domains, which represent the core of the disorder …”
Section: Discussionsupporting
confidence: 89%
“…The current study focused on interpersonal unassertiveness, which has received some support in previous research (e.g. Anderson et al 19 and Sellbom et al 55 ; but see Hopwood et al 18 ), including using traits from the FFM. 23,26 Conceptually, inclusion of unassertiveness is defensible.…”
Section: Avoidant Personality Disorder Personality Trait Profilementioning
confidence: 92%
“…Sellbom, Smid, De Saeger, Smit, and Kamphuis (2014) demonstrated that the MMPI-2-RF PSY-5 scales were significantly and meaningfully associated with PD criteria assessed through structured clinical interviews in Dutch clinical and forensic samples; many of these findings were replicated in Finn et al (2014). Similarly, added that the full set of MMPI-2-RF scales predicted DSM-5 Section II PD criteria for 7 of the 10 PDs (with sufficient variability) in those same samples.…”
Section: Assessing Personality Pathology With the Mmpimentioning
confidence: 75%
“…Right prefrontal and bilateral medial prefrontal pathology may be linked to emotional regulation difficulties or cognitive deficits in attribution or coping while the anterior insular is linked to empathy. A recent systematic review showed a link between narcissism and aggression and violence in both nonclinical and clinical samples (Lambe, Hamilton‐Giachritsis, Garner, & Walker, ). Similarly, a meta‐analysis support the association of narcissism with aggression in response to provocation, especially in those with high entitlement or vulnerable narcissism features (Rasmussen, ). The negative interpersonal impact of NPD individuals on others has recently been supported by empirical studies (Day, Bourke, Townsend, & Grenyer, 2019) and led to a proliferation of self‐help books for those involved in romantic (Behary, ; Malkin, 2015; McBride, ) parent–child (Brown, ; McBride, ) and work relationships (DuBrin, ; Eddy & DiStefano, ; Malkin, ) with NPD individuals. Research on test profile configurations (e.g., MMPI‐2‐RF) can assist the self‐report assessment of NPD (e.g., Anderson et al, ; Sellbom, Smid, De Saeger, Smit, & Kamphuis, ; Sellbom & Smith, ).…”
Section: New and Emerging Developmentsmentioning
confidence: 99%
“…• The negative interpersonal impact of NPD individuals on others has recently been supported by empirical studies (Day, Bourke, Townsend, & Grenyer, 2019) and led to a proliferation of self-help books for those involved in romantic (Behary, 2013;Malkin, 2015;McBride, 2015) parent-child (Brown, 2008;McBride, 2008) and work relationships (DuBrin, 2012;Eddy & DiStefano, 2015;Malkin, 2015) with NPD individuals. • Research on test profile configurations (e.g., MMPI-2-RF) can assist the self-report assessment of NPD (e.g., Anderson et al, 2015;Sellbom, Smid, De Saeger, Smit, & Kamphuis, 2014;Sellbom & Smith, 2017).…”
Section: New and Emerging Developmentsmentioning
confidence: 99%